Neuroanatomical alterations in tinnitus assessed with magnetic resonance imaging - Allan, Thomas W.; Besle, Julien; Langers, Dave R.M.; Davies, Jeff; Hall, Deborah A.; Palmer, Alan R.; Adjamian, Peyman (Frontiers Media, 2016)
Previous studies of anatomical changes associated with tinnitus have provided inconsistent results, with some showing significant cortical and subcortical changes, while others have found effects due to hearing loss, but not tinnitus. In this study, we examined changes in brain anatomy associated with tinnitus using anatomical scans from 128 participants with tinnitus and hearing loss, tinnitus with clinically normal hearing, and non-tinnitus controls with clinically normal hearing. The groups were matched for hearing loss, age and gender. We employed voxel- and surface-based morphometry (SBM) to investigate gray and white matter volume and thickness within regions-of-interest (ROI) that were based on the results of previous studies. The largest overall effects were found for age, gender, and hearing loss. With regard to tinnitus, analysis of ROI revealed numerous small increases and decreases in gray matter and thickness between tinnitus and non-tinnitus controls, in both cortical and subcortical structures. For whole brain analysis, the main tinnitus-related significant clusters were found outside sensory auditory structures. These include a decrease in cortical thickness for the tinnitus group compared to controls in the left superior frontal gyrus (SFG), and a decrease in cortical volume with hearing loss in left Heschl’s gyrus (HG). For masked analysis, we found a decrease in gray matter volume in the right Heschle’s gyrus for the tinnitus group compared to the controls. We found no changes in the subcallosal region as reported in some previous studies. Overall, while some of the morphological differences observed in this study are similar to previously published findings, others are entirely different or even contradict previous results. We highlight other discrepancies among previous results and the increasing need for a more precise subtyping of the condition.